Graphs in biomedical image analysis, computational anatomy and imaging genetics : first International Workshop, GRAIL 2017, 6th International Workshop, MFCA 2017, and third International Workshop, MICGen 2017, held in conjunction with MICCAI 2017, Québec City, QC, Canada, September 10-14, 2017, Proceedings /: first International Workshop, GRAIL 2017, 6th International Workshop, MFCA 2017, and third International Workshop, MICGen 2017, held in conjunction with MICCAI 2017, Québec City, QC, Canada, September 10-14, 2017, Proceedings. (2017) - Unknown
No abstract available